PENGARUH SOSIAL MEDIA MARKETING INSTAGRAM, BRAND IMAGE, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA MS GLOW (STUDI KASUS PADA KONSUMEN DISTRIBUTOR MS GLOW PANAKUKKANG DI KOTA MAKASSAR) - Shofiyah Khairunnisa; Hety Budiyanti; Muh. Ilham Wardhana Haeruddin (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2022)
This study aims to explain the influence simultaneously (together) or partially between the influence of social media marketing Instagram, brand image and product quality on purchasing decisions. This study uses a quantitative approach with survey research methods to obtain primary data. The research variables are Social Media Marketing Instagram (X1), Brand Image (X2) and Product Quality (X3) as influencing variables and Purchase Decision variable (Y) as affected variables. The population in this study are consumers of MS Glow Panakukkang users in Makassar City. The number of samples in this study were 100 consumer respondents of MS Glow Panakukkang by taking the entire population and serving as samples. The data collection method used is the distribution of questionnaires. The data analysis technique in this study used multiple regression analysis which was previously carried out with Validity, Reliability, Classical Assumption Tests (normality test, multicollinearity test, heteroscedasticity test) then tested the hypothesis through T test, F test and coefficient of determination test. The results of this study indicate that partially, Instagram social media marketing does not have a positive effect, while brand image and product quality have a positive and significant effect on purchasing decisions for MS Glow Panakukkang. Meanwhile, simultaneously the results of this study also show that social media marketing, brand image and product quality have a positive and significant effect on purchasing decisions for MS Glow Panakukkang products.